AB0143 Immunomodulation followed by quantitative transcriptional profiling to characterize the functional role of the sjÖgren's-associated ncrna ac092580.4. (15th June 2017) - Ice, JA; Adrianto, I; Rasmussen, A; Joachims, M; Johnston, A; Montgomery, C; Sivils, K; Lessard, CJ
Abstract : Background: Despite concerted efforts to characterize dysregulated transcriptional responses observed in Sjögren's syndrome and related autoimmune disorders (both in whole blood and target tissues), the functional roles of non-coding RNAs (ncRNAs), many of which have been identified as critical players in transcriptional regulation of disease, remain poorly defined. Objectives: In the present study, we describe ongoing efforts to functionally characterize the upregulated ncRNA identified by RNA-seq and in silico approaches, AC092580.4 (FC=2.54), which we hypothesize plays a role in T and NK cell responses. Methods: To study the immunomodulation of the ncRNA AC092580.4, we carried out a time-course experiment (0–36 hrs) using either PMA/I (500x dil) or universal Type I Interferon. Relative gene expression changes were determined using the Livak method by qPCR using optimized primers for GZMA and AC092580.4 normalized to GAPD . Healthy PBMCs were subjected to stimulation by PHA (1mg/mL; 3 days), PMA/I (500x dil; 3 days), or anti-CD3/CD28 (50uL/1x10 6 cells; 1 day). An average 150-bp RNA-seq reads were generated for each sample; alignment was carried out using STAR (hg38) and comparisions of stimulated vs unstimulated cells were done using DEseq. Pearson's correlation ( r ) was calculated for all 3, 748 differentially expressed (DE) transcripts to identify transcripts co-expressed with AC092580.4 . Results: Of the transcripts showing DE in our SS RNA-seq study, we identified 8 as having significantly correlated expression with AC092580.4 in the SS Ro- expression matrix ( r >0.70 or <-0.65). To understand the possible effects of immunomodulation on relevant cells, we stimulated HSB-2 cells with PMA/I at various time points and assessed AC092580.4 expression by. We observed downregulation of AC092580.4 and the co-expressed transcript GZMA by PMA/I (trough: 12–16hrs; FC=0.09) followed by slow recovery at 36hrs (FC=0.59). To characterize these transcriptional changes further, we performed RNA-seq using healthy PBMCs exposed to various T cell stimulants. We observed marked upregulation of both AC092580.4 and GZMA at 24/36hrs by all stimulants (FC=4.89–5.98). Other transcripts showed variable responses. CAV2 is upregulated by PMA/I, but downregulated by CD3/CD28 and PHA. Stimulation by PHA leads to upregulation of CD3D (FC=1.56) and SNRPD1 (FC=3.28) with little change in RPL36A (FC=1.09). Stimulation by CD3/CD28 similarly leads to upregulation of CD3D (FC=2.85) and SNRPD1 (FC=10.04), but clear downregulation of RPL36A ( FC=0.64 ) . We assessed AC092580.4 expression in HSB-2 cells exposed to I IFN and observed initial upregulation (6hrs, FC=1.46) followed by gradual downregulation (36hrs, FC=0.18). Conclusions: In the present study, we have initiated stimulation studies with to understand the immune relevance of AC092580.4 and co-expressed targets. AC092580.4 shows transcriptional induction by potent inducers of T cell responses (PMA/I, PHA, CD3/CD28) but is downregulated by type I IFN. Transcripts showing co-expressed with AC092580.4 by whole-blood RNA-seq show divergent expression patterns according to the specific stimulus, suggesting a complex regulatory network governing dysregulated T and NK responses. Disclosure of Interest: None declared